Fighting African Capital Flight: Empirics on Benchmarking Policy Harmonization - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2013)
With earthshaking and heartbreaking trends in African capital flight provided by a new database, this paper complements existing literature by answering some key policy questions on the feasibility of and timeframe for policy harmonization in the battle against the economic scourge. The goal of the paper is to study beta-convergence of capital flight across a set of 37 African countries in the period 1980-2010 and to discuss the policy implications. Three main findings are established. (1) African countries with low capital flight rates are catching-up their counterparts with higher rates, implying the feasibility of policy harmonization towards fighting capital flight. (2) Petroleum-exporting and conflict-affected countries significantly play out in absolute and conditional convergences respectively. (3) Regardless of fundamental characteristics, a genuine timeframe for harmonizing policies is within a horizon of 6 to 13 years. In other words, full (100%) convergence within the specified horizon is an indication that policies and regulations can be enforced without distinction of nationality or locality.
Keywords: C50; E62; F34; O19; O55; 330; Econometric modeling; Big push; Capital flight; Debt relief; Africa